2013
DOI: 10.1016/j.ccr.2013.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Tumor Angiogenesis and Growth by a Small-Molecule Multi-FGF Receptor Blocker with Allosteric Properties

Abstract: Receptor tyrosine kinases (RTK) are targets for anticancer drug development. To date, only RTK inhibitors that block orthosteric binding of ligands and substrates have been developed. Here, we report the pharmacologic characterization of the chemical SSR128129E (SSR), which inhibits fibroblast growth factor receptor (FGFR) signaling by binding to the extracellular FGFR domain without affecting orthosteric FGF binding. SSR exhibits allosteric properties, including probe dependence, signaling bias, and ceiling e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
107
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(117 citation statements)
references
References 50 publications
5
107
0
5
Order By: Relevance
“…Interestingly, at variance with the hyperphosphatemic effect of FGFR TK inhibitors in preclinical models [157] and cancer patients [146], long-term administration of the small molecule FGF trap NSC12 does not affect the blood levels of phosphorus, calcium and FGF23 in tumor-bearing mice [120]. These observations are in keeping with the safety profile in murine tumor models of the FGFR1-derived FGF trap FP-1039 [124] and of the allosteric multi-FGFR blocker SSR128129E [148]. Together, these findings suggest that hyperphosphatemia may represent a side effect of FGFR TK inhibitors rather than of extracellular inhibitors of the FGF/FGFR system.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Interestingly, at variance with the hyperphosphatemic effect of FGFR TK inhibitors in preclinical models [157] and cancer patients [146], long-term administration of the small molecule FGF trap NSC12 does not affect the blood levels of phosphorus, calcium and FGF23 in tumor-bearing mice [120]. These observations are in keeping with the safety profile in murine tumor models of the FGFR1-derived FGF trap FP-1039 [124] and of the allosteric multi-FGFR blocker SSR128129E [148]. Together, these findings suggest that hyperphosphatemia may represent a side effect of FGFR TK inhibitors rather than of extracellular inhibitors of the FGF/FGFR system.…”
Section: Discussionsupporting
confidence: 71%
“…Apart from intracellular-acting TKIs, recent observations have shown that the small molecule SSR128129E can bind the extracellular portion of FGFRs and inhibit FGFR signalling by an allosteric mechanism of action, without affecting the orthosteric binding of FGF to the receptor [148].…”
Section: Inhibition Of Signal Transduction Triggered By Fgfr Activationmentioning
confidence: 99%
“…Таким блокатором является, например, Довитиниб (TKI258, Новартис) -ингибитор рецепторных тирозинкиназ FLT3, KIT, FGFR, VEGFR, PDGFRa и PDGFRb. Кроме того, уже разрешено проведение клинических испытаний ингибитора киназы FGFR -BGJ398 (Новартис), в комбинации с другими химиотерапевтическими препаратами при ряде тяжелых нелеченных онкологических заболеваниях, в том числе аденокарциноме поджелудочной железы стадий III и IV [58,59]. Подобные блокаторы элементов FGF c повышенной активностью при раке поджелудочной железы могли бы быть полезны при его терапии.…”
Section: заключение и выводыunclassified
“…En effet, ces inhibiteurs possèdent des propriétés avantageuses : (1) compte tenu de leur affinité plus faible, ils sont généralement plus efficaces et plus sélectifs que les inhibiteurs orthosté-riques ; (2) ils ne sont pas actifs lorsque le ligand endogène n'est pas présent, limitant ainsi les effets indésirables [4][5][6][7][8]. Dans deux articles publiés récemment dans Cancer Cell [9,10] Concernant les inhibiteurs des tyrosine kinases, indépendamment du fait que leur sélectivité vis-à-vis d'un récepteur donné est difficile à obtenir, ces composés inhibent complètement la signalisation cellulaire induite par la fixation du ligand endogène au récepteur RTK. Dans ce contexte, la cellule, et en particulier la cellule tumorale, met en place des mécanismes de compensation visant à utiliser d'autres récepteurs et voies sion récente du dialogue entre la tumeur et son environnement et de son implication dans la résistance aux traitements, dans le processus métastatique et l'angiogenèse, permet de penser que les modèles orthotopiques (implantation de tumeurs au sein de l'organe d'origine) pourraient être plus informatifs que les modèles classiquement utilisés (implantation sous-cutanée) pour éva-luer l'efficacité du SSR.…”
unclassified
“…Ainsi, dans différents modèles de cancer réalisés après implantation orthotopique de cellules tumorales, le traitement par le SSR (par voie orale) bloque à la fois la croissance tumorale et l'apparition de métastases. Cette efficacité est également observée vis-à-vis de tumeurs résistantes aux anti-VEGF [9].…”
unclassified